METHOD FOR MANUFACTURING A MONOLITHIC CATALYST FOR SIMULTANEOUS REMOVAL OF NOX AND CARBON PARTICLES, ESPECIALLY FROM OFF-GASES OF CARBON POWER PLANTS - WESELUCHA-BIRCZYNSKA Aleksandra; BIELANSKA Elzbieta; DUTKIEWICZ Jaroslaw; DANKO Janusz; NAJBAR Mieczyslawa; WILKOSZ Tomasz; CAMRA Jozef; BARTYZEL Jakub (2019)
The manner of production of the monolithic catalyst for simultaneous removal of NOx and carbon particles, especially from off-gases of carbon power plants depends on the monolith is subject to oxidation after which the resulting oxide layers are washed with the solution of nickel salts; later the monolith is baked in the oxidising atmosphere with the view to inserting nickel ions into the oxide layer; finally this obtained oxide layers are subject to reduction.